Vacuum plating-based forming process of fabric optical film layer
Patent Information
- Application Number
- CN202611345682.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]此外,Al反射层暴露于外界时容易受到氧化、摩擦和刮擦影响
[0029]1.现有直接金属化工艺在柔性高分子表层与Al反射层之间形成突变界面,活化表面在空气暴露后还可能发生时效回落。本发明采用Ar/O2等离子体对柔性高分子表层进行活化,并在活化结束后维持真空状态形成富碳初始区,使活化界面直接与较柔顺的有机硅初始组成相结合,有利于提高基材与后续膜层之间的结合稳定性。
Smart Images

Figure CN122879647A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible material surface treatment and vacuum optical coating technology, and in particular to a fabric optical film forming process based on vacuum coating. Background Technology
[0002] Flexible fabrics such as shoe uppers with TPU surfaces and nylon fabrics possess characteristics such as bendability, significant surface undulations, and low heat resistance. To achieve a metallic reflective appearance on these fabric surfaces, metal layers can be deposited using methods such as vacuum evaporation and magnetron sputtering. Compared to rigid plastic or glass substrates, flexible polymer surfaces are prone to localized softening, dimensional changes, and interfacial shear deformation during vacuum processing and repeated bending. The significant differences in composition and mechanical properties between the metal film and the flexible substrate further amplify these problems.
[0003] In existing processes, when a metal film is directly formed on the surface of a flexible polymer, the interface between the metal layer and the substrate easily becomes a stress concentration point, potentially leading to network cracks, localized detachment, or large-area peeling after bending. While using a uniformly composed silicone layer as an interlayer can improve surface coverage, the substrate-side and metal-side of this uniform layer have similar compositions, making it difficult to simultaneously achieve both flexible adhesion and dense load-bearing capacity. When simply stacking carbon-rich and oxygen-rich layers, an abrupt interface still exists between the two layers, where interlayer shear stress generated by repeated bending easily concentrates.
[0004] Furthermore, the Al reflective layer is susceptible to oxidation, friction, and scratches when exposed to the external environment. Using higher temperatures to form a dense protective layer may soften or shrink the thermoplastic polymer surface layer. Therefore, it is necessary to synergistically design the interfacial state of the flexible polymer surface layer, the thickness direction composition of the silicone interlayer, and the outer protective structure to improve the interfacial bonding stability, flexural retention, and surface durability of the film layer at lower substrate temperatures. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a fabric optical film forming process based on vacuum coating.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A fabric optical film forming process based on vacuum coating includes the following steps:
[0008] The fabric substrate with a flexible polymer surface is placed in a vacuum reaction chamber. After evacuation, Ar and O2 are introduced to activate the flexible polymer surface through plasma.
[0009] After plasma activation is completed, the vacuum reaction chamber is kept in a vacuum state. TMDSO and O2 are switched in the same vacuum reaction chamber, while keeping the set values of TMDSO flow rate and radio frequency power unchanged.
[0010] Plasma-enhanced chemical vapor deposition is performed at a first O2 / TMDSO flow ratio to form a carbon-rich initial region on the flexible polymer surface. During continued deposition, the O2 / TMDSO flow ratio is continuously increased from the first O2 / TMDSO flow ratio to a second O2 / TMDSO flow ratio to form a continuous composition gradient region with continuously varying composition along the film thickness direction. Subsequently, deposition continues at the second O2 / TMDSO flow ratio to form an oxygen-rich outer region, thereby obtaining an organosilicon transition layer that sequentially includes the carbon-rich initial region, the continuous composition gradient region, and the oxygen-rich outer region.
[0011] An Al reflective layer was formed on the oxygen-rich outer region using physical vapor deposition.
[0012] A transparent organosilicon protective layer is formed on the Al reflective layer by plasma-enhanced chemical vapor deposition at a third O2 / TMDSO flow ratio.
[0013] Wherein, the second O2 / TMDSO flow ratio is greater than the first O2 / TMDSO flow ratio, and the third O2 / TMDSO flow ratio is greater than the first O2 / TMDSO flow ratio; the thickness of the continuous gradient region is greater than the thickness of the carbon-rich initial region and the oxygen-rich outer region, respectively; during the plasma activation and each film layer forming process, the maximum temperature of the fabric substrate does not exceed 60°C.
[0014] The fabric substrate with a flexible polymer surface layer refers to a fabric with a flexible polymer coating on its surface, or a fabric whose surface is composed of flexible polymer fibers. Preferably, the fabric substrate is a TPU-coated nylon fabric.
[0015] In this invention, the first O2 / TMDSO flow rate ratio, the second O2 / TMDSO flow rate ratio, and the third O2 / TMDSO flow rate ratio all refer to the ratio of the O2 gas volumetric flow rate to the TMDSO gas volumetric flow rate during the corresponding deposition stage. Keeping the TMDSO flow rate and RF power settings constant means that the TMDSO flow rate and RF power are not actively changed during the deposition of the organosilicon transition layer, and the O2 / TMDSO flow rate ratio is changed by continuously adjusting the O2 flow rate.
[0016] The continuous increase in the O2 / TMDSO flow ratio refers to the process of depositing the continuous composition gradient region, in which the O2 / TMDSO flow ratio changes continuously and monotonically from the first O2 / TMDSO flow ratio to the second O2 / TMDSO flow ratio with the deposition time or equivalent deposition thickness, so that the proportions of carbon, oxygen and Si-O structures in the film layer change continuously along the thickness direction.
[0017] The carbon-rich initial region and the oxygen-rich outer region are regions determined based on the relative compositional relationship within the organosilicon transition layer. The carbon-rich initial region has a higher carbon atom ratio than the oxygen-rich outer region, exhibiting a greater proportion of organic carbon structures; the oxygen-rich outer region has a higher oxygen atom ratio and a higher Si-O structure ratio than the carbon-rich initial region. The oxygen-rich outer region is not limited to a carbon-free inorganic silicon oxide layer.
[0018] Plasma activation and organosilicon transition layer deposition are carried out continuously in the same vacuum reaction chamber, ensuring that the activated flexible polymer surface layer does not come into contact with the outside air before the formation of the carbon-rich initial region. The Al reflective layer can be formed in the same composite vacuum equipment with physical vapor deposition capabilities, or it can be transferred to a physical vapor deposition equipment after the formation of the organosilicon transition layer.
[0019] Preferably, the fabric substrate is a TPU-coated nylon fabric, and the flexible polymer surface layer is a TPU surface layer.
[0020] Preferably, radio frequency plasma is used for plasma activation, with an Ar to O2 volume ratio of 3:1 to 9:1, an activation pressure of 10 to 40 Pa, a radio frequency power of 40 to 100 W, and an activation time of 30 to 120 s.
[0021] Preferably, the first O2 / TMDSO flow ratio is 0.8 to 1.5, the second O2 / TMDSO flow ratio is 3 to 5, and the total thickness of the organosilicon transition layer is 60 to 180 nm.
[0022] Preferably, during the deposition of the continuous composition gradient region, the O2 flow rate is continuously increased, so that the O2 / TMDSO flow rate ratio increases linearly from the first O2 / TMDSO flow rate ratio to the second O2 / TMDSO flow rate ratio with the deposition time.
[0023] Preferably, the working pressure during the formation of the organosilicon transition layer is 20–60 Pa, and the radio frequency power is 50–100 W.
[0024] Preferably, the Al reflective layer is formed by DC magnetron sputtering, and the thickness of the Al reflective layer is 20-50 nm.
[0025] Preferably, the third O2 / TMDSO flow ratio is 3–6, and the thickness of the transparent organosilicon protective layer is 60–200 nm. The transparent organosilicon protective layer has a higher oxygen content and Si-O structure ratio compared to the carbon-rich initial region, serving to isolate the Al reflective layer from the external environment and improve the film's wear resistance and optical appearance stability.
[0026] The total thickness of the silicone transition layer, the Al reflective layer, and the transparent silicone protective layer can be measured using a flat Si witness sheet placed in the same batch and position as the fabric substrate. A film layer step is formed by creating a shielded area on the Si witness sheet, and the film layer thickness is measured using a contact profilometer. The thicknesses of the continuous composition gradient region, the carbon-rich initial region, and the oxygen-rich outer region can be determined based on the deposition rate and deposition time under the corresponding deposition conditions, and are used as the equivalent deposition thickness.
[0027] The highest temperature of the fabric substrate can be measured using a temperature sensor fixed to the center area of the back of a representative fabric sample, avoiding the fixture and the edge of the sample during measurement. The temperature recording period starts from plasma activation and continues until the deposition of the transparent silicone protective layer. When multiple vacuum processing chambers are used, the highest temperature measured in each vacuum processing stage is taken as the highest temperature of the fabric substrate.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] 1. Existing direct metallization processes create abrupt interfaces between the flexible polymer surface and the Al reflective layer, and the activated surface may experience aging degradation after air exposure. This invention uses Ar / O2 plasma to activate the flexible polymer surface and maintains a vacuum state after activation to form a carbon-rich initial region. This allows the activated interface to directly bond with the relatively compliant initial composition of the organosilicon, which is beneficial for improving the bonding stability between the substrate and subsequent film layers.
[0030] 2. Existing uniform composition intermediate layers or abrupt double layers struggle to simultaneously achieve both compliant matching on the substrate side and dense load-bearing on the metal side. This invention continuously increases the O2 / TMDSO flow ratio while maintaining constant TMDSO flow and RF power settings, and makes the continuous composition gradient region thicker than the constant ratio regions at both ends. This allows the organosilicon transition layer to gradually transform from a carbon-rich composition to an oxygen-rich, Si-O-rich composition, reducing abrupt changes in film composition and mechanical properties, and minimizing stress concentration and interlayer shear delamination at single interfaces during repeated bending.
[0031] 3. The Al reflective layer is prone to appearance changes under external friction and oxidation, and high-temperature protection processes can easily affect thermoplastic fabrics. This invention forms a transparent organosilicon protective layer outside the Al reflective layer and controls the maximum substrate temperature during plasma activation and each film layer forming process to below 60°C. This maintains the metallic reflective appearance while improving surface abrasion resistance and reducing substrate softening, shrinkage, and warping. Attached Figure Description
[0032] Figure 1 The high-resolution X-ray photoelectron spectrum and peak fitting diagram of the TPU sample (sample W1) after activation by Ar / O2 plasma. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0034] Raw materials and equipment:
[0035] The main substrate used in this example is TPU-coated nylon fabric, with a TPU surface layer thickness of approximately 45 μm and a total fabric thickness of approximately 0.40 mm. The process gases are Ar and O2, both with a purity of not less than 99.99%; the organosilicon precursor is 1,1,3,3-tetramethyldisiloxane (TMDSO); and the Al target material has a purity of not less than 99.99%.
[0036] Plasma activation and silicone layer deposition were carried out in a low-pressure RF plasma / PECVD reaction chamber that could introduce Ar, O2 and TMDSO and had mass flow control and substrate temperature monitoring functions. The Al reflective layer was formed using a DC magnetron sputtering device.
[0037] Example 1: A fabric optical film forming process based on vacuum coating, comprising the following steps:
[0038] Take three pieces of TPU-coated nylon fabric measuring 100mm × 150mm, wet a lint-free cloth with isopropyl alcohol and gently wipe the coated surface in one direction, then dry at 45℃ for 20 minutes. After cooling, fix the fabric sample and the Si witness sheet onto a low-tension flat fixture.
[0039] The sample was placed into the vacuum reaction chamber and evacuated to a pressure not exceeding 1 Pa. Ar and O2 were introduced, and the volume flow rate ratio of Ar to O2 was adjusted to 4:1. Plasma activation was carried out at a working pressure of 20 Pa and a radio frequency power of 80 W for 60 s.
[0040] After plasma activation, maintain the vacuum state of the vacuum reaction chamber without opening the chamber, and switch the flow of TMDSO and O2. Adjust the working pressure to 30 Pa, keep the RF power at 80 W, and keep the TMDSO flow rate and RF power settings constant during the deposition of the silicone transition layer.
[0041] First, the O2 / TMDSO flow ratio was kept at 1 to deposit a carbon-rich initial region with a thickness of 20 nm. Then, the O2 flow rate was continuously increased so that the O2 / TMDSO flow ratio increased linearly from 1 to 4 with the deposition time, and a continuous compositional gradient region with a thickness of 60 nm was deposited. Then, the O2 / TMDSO flow ratio was kept at 4 to deposit an oxygen-rich outer region with a thickness of 20 nm, resulting in an organosilicon transition layer with a total thickness of 100 nm.
[0042] The sample with the formed organosilicon transition layer is transferred into a DC magnetron sputtering apparatus, and the apparatus is evacuated to a vacuum level not exceeding 5 × 10⁻⁶. -3 Pa, Ar was introduced and the working pressure was adjusted to 0.5 Pa, and an Al reflective layer with a thickness of 30 nm was formed at a sputtering power of 80 W.
[0043] Subsequently, plasma-enhanced chemical vapor deposition was performed on the Al reflective layer at an O2 / TMDSO flow ratio of 4 to form a transparent silicone protective layer with a thickness of 100 nm. During plasma activation and the formation of each film layer, the maximum temperature of the fabric substrate did not exceed 60°C.
[0044] After the transparent silicone protective layer was deposited, the sample was taken out and placed in a clean bag in the dark for 24 hours to obtain the fabric optical film sample of Example 1, which is denoted as E1.
[0045] Example 2:
[0046] This embodiment uses the same TPU-coated nylon fabric, cleaning method, plasma activation conditions, Al reflective layer molding conditions, and transparent silicone protective layer molding conditions as in Embodiment 1.
[0047] In this embodiment, the total thickness of the organosilicon transition layer is 150 nm. First, the O2 / TMDSO flow ratio is kept at 1 to deposit a carbon-rich initial region with a thickness of 30 nm. Then, the O2 flow rate is continuously increased so that the O2 / TMDSO flow ratio increases linearly from 1 to 4 with the deposition time, depositing a continuous compositional gradient region with a thickness of 90 nm. Then, the O2 / TMDSO flow ratio is kept at 4 to deposit an oxygen-rich outer region with a thickness of 30 nm.
[0048] After the transparent silicone protective layer was deposited, the sample was taken out and placed in a clean bag in the dark for 24 hours to obtain the fabric optical film sample of Example 2, which is denoted as E2.
[0049] Example 3:
[0050] In this embodiment, bare nylon fabric is used as the fabric substrate, and the fabric surface is composed of nylon fibers. Except for the type of substrate, the preparation conditions for fabric cleaning, plasma activation, silicone transition layer, Al reflective layer, and transparent silicone protective layer are the same as in Example 1.
[0051] After the transparent silicone protective layer was deposited, the sample was taken out and placed in a clean bag in the dark for 24 hours to obtain the fabric optical film sample of Example 3, which is denoted as E3.
[0052] The following comparison model was also set:
[0053] Comparative Example 1:
[0054] This comparative example uses the same TPU-coated nylon fabric as Example 1, without Ar / O2 plasma activation or the formation of an organosilicon transition layer. Instead, a 30nm thick Al reflective layer is directly formed on the TPU surface, and a 100nm thick transparent organosilicon protective layer is formed on the Al reflective layer.
[0055] The preparation conditions for the Al reflective layer and the transparent silicone protective layer were the same as in Example 1, and the resulting sample was denoted as D1.
[0056] Comparative Example 2:
[0057] This comparative example uses the same TPU-coated nylon fabric as Example 1, and undergoes Ar / O2 plasma activation under the conditions of Example 1. After plasma activation, no silicone transition layer is formed; instead, a 30 nm thick Al reflective layer is directly formed, and a 100 nm thick transparent silicone protective layer is formed on the Al reflective layer.
[0058] The remaining preparation conditions were the same as in Example 1, and the resulting sample was denoted as D2.
[0059] Comparative Example 3:
[0060] This comparative example uses the same TPU-coated nylon fabric and plasma activation conditions as Example 1. After plasma activation, the vacuum state of the vacuum reaction chamber is maintained, TMDSO and O2 are introduced, and the O2 / TMDSO flow ratio is maintained at 2.5 to deposit a uniform composition organosilicon transition layer with a total thickness of 100 nm.
[0061] Subsequently, an Al reflective layer with a thickness of 30 nm and a transparent organosilicon protective layer with a thickness of 100 nm were formed. Except for the composition control method of the organosilicon transition layer, the other preparation conditions were the same as in Example 1, and the resulting sample was designated as D3.
[0062] Comparative Example 4:
[0063] This comparative example uses the same TPU-coated nylon fabric and plasma activation conditions as Example 1. After plasma activation, the vacuum state of the vacuum reaction chamber is maintained. First, an organosilicon layer with a thickness of 50 nm is deposited with an O2 / TMDSO flow ratio of 1. Then, the O2 / TMDSO flow ratio is directly switched to 4, and an organosilicon layer with a thickness of 50 nm is deposited to form a bilayer organosilicon transition layer with a total thickness of 100 nm and a compositional abrupt interface.
[0064] Subsequently, an Al reflective layer with a thickness of 30 nm and a transparent organosilicon protective layer with a thickness of 100 nm were formed. Except for the composition control method of the organosilicon transition layer, the other preparation conditions were the same as in Example 1, and the resulting sample was designated as D4.
[0065] Performance testing:
[0066] 1. Measurement of film thickness and deposition rate:
[0067] The thicknesses of the silicone transition layer, Al reflective layer, and transparent silicone protective layer were measured using Si witness sheets placed in the same batch as the fabric samples. Before testing, a masking area was set on the Si witness sheet. After deposition, the masking material was removed to form film steps, and the film thickness was measured using a contact step meter.
[0068] The thicknesses of the carbon-rich initial region, the continuous compositional gradient region, and the oxygen-rich outer region were determined based on pre-calibrated deposition rates and times under the corresponding deposition conditions. Silicone films were deposited at O2 / TMDSO flow ratios of 1 and 4, respectively, and the deposition rate was calculated using the measured film thickness and deposition time. Under the central process conditions used in this embodiment, the silicone deposition rates at O2 / TMDSO flow ratios of 1 and 4 were 22.5 nm / min and 12.0 nm / min, respectively, and the Al deposition rate was 15.0 nm / min.
[0069] 2. Measurement of the highest temperature of the substrate:
[0070] The temperature sensor was fixed to the center of the back of a representative fabric sample, avoiding the fixture and the edges of the sample. Temperature recording began with plasma activation and continued until the deposition of the transparent silicone protective layer.
[0071] When multiple vacuum treatment chambers are used, the substrate temperature of each vacuum treatment stage is recorded, and the highest temperature measured in each stage is taken as the highest temperature of the fabric substrate.
[0072] 3. X-ray photoelectron spectroscopy:
[0073] X-ray photoelectron spectroscopy (XPS) tests include Survey spectroscopy, C1s spectroscopy, O1s spectroscopy, and Si2p spectroscopy. Each sample uses the same charge correction method, background type, and peak shape constraint.
[0074] The C and O elemental composition and C1s peak were determined for TPU samples before and after activation; the C, O, and Si elemental composition and Si-O related signals were determined for Si witness samples whose deposition was terminated at different stages of the organosilicon transition layer.
[0075] 4. Optical performance testing:
[0076] Optical testing was performed using d / 8 geometry, SCI mode, D65 light source, and 10° observation. Three fixed test positions were selected for each sample, and the reflectance spectrum and L*, a*, and b* values in the range of 400–700 nm were recorded.
[0077] The same area was measured using a positioning template before and after bending. The visible light reflectance retention rate was calculated as the ratio of the average visible light reflectance after bending to the average visible light reflectance before bending. The overall color difference ΔE before and after bending was calculated according to CIEDE2000. 00 .
[0078] 5. Reciprocating bending test:
[0079] The sample was cut into 50mm×100mm bending specimens with the coated side facing outwards, and bent 180° back and forth around a circular shaft with a radius of 5mm. The bending frequency was 30 times / min, and the number of cycles was 1000.
[0080] The test environment temperature was 23±2℃ and the relative humidity was 50±10%. Before the test, the sample was conditioned in the above environment for no less than 2 hours. After bending, it was left to stand for 30 minutes before optical detection at the same point and tape retention rate detection were performed.
[0081] 6. Tape retention rate test:
[0082] The sample was fixed on a flat, rigid backing plate, and a test area of 25mm × 50mm was selected. Transparent pressure-sensitive tape from the same batch was used, with a 180° peel strength rating of 40–50 N / 100mm.
[0083] The tape was applied to the test area and rolled back and forth twice using a 2kg roller. After standing for 90 seconds, the tape was peeled off at a peel angle of 180° and a peel speed of 300mm / min. The area of film detachment was calculated using images taken before and after peeling under fixed lighting conditions. The film retention rate P was calculated using the following formula:
[0084] P = [1 - area of film peeling / test area] × 100%.
[0085] The film retention rate of the sample without repeated bending is recorded as the initial tape retention rate, and the film retention rate of the sample after 1000 repeated bending cycles is recorded as the tape retention rate after bending.
[0086] 7. Abrasion resistance test:
[0087] Directional abrasion resistance testing was conducted using the Martindale method, with a test pressure of 9 kPa, a dry testing condition, and 500 cycles. After the test, the overall color difference ΔE in the abrasion-resistant area was measured. 00 And observe the damage to the film surface.
[0088] XPS test results:
[0089] To verify the plasma activation and compositional changes of the organosilicon transition layer along the thickness direction, the following test samples were set up:
[0090] W0 is an untreated TPU sample; W1 is a TPU sample activated by Ar / O2 plasma; W2, W3, and W4 are Si witness wafers whose deposition was terminated at 20 nm, approximately 50 nm, and 100 nm, respectively, in the organosilicon transition layer. Figure 1 As shown, the high-resolution C1s spectrum of sample W1 can be fitted with four components: CC / CH, CO, C=O, and OC=O.
[0091] The test results are shown in Table 1.
[0092] The tape retention rate, optical properties after bending, and abrasion resistance of each embodiment and comparative example are shown in Table 2.
[0093] Table 1. Elemental composition of XPS in plasma-activated and organosilicon transition layers
[0094] ;
[0095] Table 2. Bending, adhesion, and abrasion resistance properties of the examples and comparative examples
[0096] .
[0097] Data Analysis:
[0098] like Figure 1 As shown in Table 1, the high-resolution C1s spectrum of sample W1 after Ar / O2 plasma activation can be divided into four components: CC / CH, CO, C=O, and OC=O. After plasma activation, the O / C atomic ratio on the TPU surface increased from 0.214 to 0.404; the proportions of CO, C=O, and OC=O components in sample W0 were 16.2%, 7.1%, and 2.2%, respectively, while the proportions of the corresponding components in sample W1 increased to 25.8%, 14.1%, and 8.0%, respectively. These results indicate that Ar / O2 plasma activation increases the oxygen-containing carbon structure on the TPU surface, providing more polar and reaction sites for the subsequent interfacial bonding between the carbon-rich initial region and the fabric substrate coating surface.
[0099] The carbon atom ratio in samples W2 to W4 gradually decreased from 39.5 at% to 17.5 at%, while the oxygen atom ratio gradually increased from 34.2 at% to 53.1 at%, with a corresponding enhancement in Si-O related characteristics. This change corresponds to the process of continuously increasing O2 / TMDSO flow ratio during the deposition of the organosilicon transition layer, indicating that the organosilicon transition layer gradually transforms from a carbon-rich initial region to an oxygen-rich outer region along the deposition direction.
[0100] As shown in Table 2, Comparative Example 1, without plasma activation and without an organosilicon transition layer, had an initial tape retention rate of 72.5%, but after bending, the tape retention rate was only 16.0%, and large-area peeling occurred at the TPU / Al interface. Comparative Example 2, after adding Ar / O2 plasma activation, saw an increase in the initial tape retention rate to 89.0% and the tape retention rate after bending to 44.5%, indicating that surface activation is beneficial for improving the bonding stability between the film layer and the TPU surface.
[0101] Comparative Example 3 used a uniformly composed silicone transition layer, and the tape retention rate after bending increased to 71.0%; Comparative Example 4 used a mutated bilayer silicone transition layer, and the tape retention rate after bending increased to 78.5%. These results indicate that the silicone transition layer can further improve film retention, but the uniformly composed layer and the mutated bilayer still exhibit stress concentration and interlayer shear delamination phenomena, respectively.
[0102] The total thickness of the silicone transition layer in Example 1 was 100 nm, with the continuous compositional gradient region being thicker than the carbon-rich initial region and the oxygen-rich outer region. The tape retention rate after bending in Example 1 was 94.5%, an increase of 23.5 percentage points compared to Comparative Example 3 and 16.0 percentage points compared to Comparative Example 4; the visible light reflectance retention rates increased by 13.7 and 10.2 percentage points, respectively, and the overall color difference decreased by 2.10 and 1.40, respectively. These results indicate that continuously changing the composition along the film thickness direction and ensuring that the continuous compositional gradient region occupies the main thickness is beneficial for reducing interfacial mismatch during repeated bending of the flexible substrate.
[0103] Example 2, by increasing the total thickness of the silicone transition layer to 150 nm, still maintained high tape retention and visible light reflectance after bending. The overall color difference after 500 dry abrasion cycles for Examples 1 and 2 were 0.85 and 0.80, respectively, indicating that the complete film system with the transparent silicone protective layer still exhibits good optical appearance stability after friction. Example 3 also achieved high tape retention and visible light reflectance after bending on bare nylon fabric, indicating that the process can be used on fabric substrates with a nylon surface.
[0104] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A fabric optical film forming process based on vacuum coating, characterized in that, Includes the following steps: S1. Surface activation: The fabric substrate is placed in a vacuum reaction chamber, and after the vacuum reaction chamber is evacuated, Ar and O2 are introduced to activate the coating surface of the fabric substrate through plasma. S2, Deposition of Organosilicon Transition Layer: S2.
1. Maintain the vacuum state of the vacuum reaction chamber, switch the gas supply in the vacuum reaction chamber to 1,1,3,3-tetramethyldisiloxane (TMDSO) and O2, and perform plasma-enhanced chemical vapor deposition; during the deposition of the organosilicon transition layer, keep the TMDSO flow rate and RF power settings constant, and first deposit a carbon-rich initial region with a first O2 / TMDSO flow rate ratio; S2.
2. Continuously increase the O2 flow rate, so that the O2 / TMDSO flow rate ratio continuously increases from the first O2 / TMDSO flow rate ratio to the second O2 / TMDSO flow rate ratio, and deposit to form a continuous composition gradient region with continuously changing composition along the thickness direction; S2.
3. Continue deposition at the second O2 / TMDSO flow ratio to form an oxygen-rich outer zone; The organosilicon transition layer is composed of the carbon-rich initial region, the continuous composition gradient region, and the oxygen-rich outer region; the total thickness of the organosilicon transition layer is 60-180 nm, wherein the thickness ratio of the carbon-rich initial region, the continuous composition gradient region, and the oxygen-rich outer region is 1:3:
1. S3. Reflective layer deposition: Using an Al target and Ar as the sputtering gas, an Al reflective layer is formed on the organosilicon transition layer by DC magnetron sputtering. S4. Protective layer deposition: Using TMDSO and O2 as reactive gases, plasma-enhanced chemical vapor deposition is performed on the Al reflective layer at a third O2 / TMDSO flow ratio to form a transparent organosilicon protective layer. Wherein, the first O2 / TMDSO flow ratio is 0.8 to 1.5, the second O2 / TMDSO flow ratio is 3 to 5, and the third O2 / TMDSO flow ratio is 3 to 6; the thickness of the transparent silicone protective layer is 60 to 200 nm; during steps S1 to S4, the temperature of the fabric substrate does not exceed 60°C.
2. The fabric optical film forming process according to claim 1, characterized in that, The fabric substrate is TPU, EVA or nylon.
3. The fabric optical film forming process according to claim 1, characterized in that, The plasma activation is radio frequency plasma activation, with an Ar to O2 volume flow rate ratio of 3:1 to 9:1, a working pressure of 10 to 40 Pa, a radio frequency power of 40 to 100 W, and a processing time of 30 to 120 s.
4. The fabric optical film forming process according to claim 1, characterized in that, During the deposition of the continuous composition gradient region, the O2 flow rate is continuously increased, so that the O2 / TMDSO flow rate ratio increases linearly from the first O2 / TMDSO flow rate ratio to the second O2 / TMDSO flow rate ratio with the deposition time.
5. The fabric optical film forming process according to claim 1, characterized in that, The working pressure during the formation of the organosilicon transition layer is 20-60 Pa, and the radio frequency power is 50-100 W.
6. The fabric optical film forming process according to claim 1, characterized in that, The operating pressure of the DC magnetron sputtering cavity is 0.3–0.8 Pa, the sputtering power is 50–150 W, and the thickness of the Al reflective layer is 20–50 nm.
7. The fabric optical film forming process according to claim 1, characterized in that, The working pressure during the formation of the transparent silicone protective layer is 20-60 Pa, and the radio frequency power is 50-100 W.
8. The fabric optical film forming process according to claim 1, characterized in that, Before plasma activation, the coated surface of the fabric substrate is cleaned with isopropanol and dried at 40–50°C for 15–30 min.